Creatures : [large type] a novel - Van Meter, Crissy (Thorndike press large print reviewers' choice, 2020)
""Inventive and surprising . . . A punch to the heart. It's one of the best novels I've read this year." --Kristen Arnett, bestselling author of Mostly Dead Things On the eve of Evangeline's wedding, on the shore of Winter Island, a dead whale is trapped in the harbor, the groom may be lost at sea, and Evie's mostly absent mother has shown up out of the blue. From there, in this mesmerizing, provocative debut, the narrative flows back and forth through time as Evie reckons with her complicated upbringing in this lush, wild land off the coast of Southern California. Evie grew up with her well-meaning but negligent father, surviving on the money he made dealing the island's world-famous strain of weed, Winter Wonderland. Although her father raised her with a deep respect for the elements, the sea, and the creatures living within it, he also left her to parent herself. With wit, love, and bracing flashes of anger, Creatures probes the complexities of love and abandonment, guilt and forgiveness, betrayal and grief--and the ways in which our childhoods can threaten our ability to love if we are not brave enough to conquer the past. Lyrical, darkly funny, and ultimately cathartic, Creatures exerts a pull as strong as the tides"--